A Mixed Method Study On The Associating Factors, Reasons For Use, Perceptions And Quitting Behaviour Of E-Cigarette Among Dual Users In Malaysia - Mat Ruzlin, Aimi Nadira (2023)
Several sociodemographic and smoking related factors have a significant association with dual use and its frequency of use. In addition, further investigation in phase II found that dual use was detrimental to its users. The findings from this study provide essential information to plan future preventive measures as well as recommendations for EC legislation in Malaysia.